Symmetry-governed dynamics of magnetic skyrmions under field pulses - Vladyslav M. Kuchkin; Bruno Barton-Singer; Pavel F. Bessarab; Nikolai S. Kiselev (Communications Physics)
Abstract Topological magnetic solitons, such as skyrmions, exhibit intriguing particle-like properties that make them attractive for fundamental research and practical applications. While many magnetic systems can host skyrmions as statically stable configurations, chiral magnets stand out for their ability to accommodate a wide diversity of skyrmions with arbitrary topological charges and varied morphologies. Despite extensive investigation, a complete understanding of chiral magnetic skyrmions has remained elusive. We present a classification of all chiral skyrmions, demonstrating three classes based on their response to external magnetic field pulses: stationary, translating, and rotating. We highlight the role of magnetic texture symmetry in this classification. Skyrmions with varied dynamics offer avenues for exploring phenomena like skyrmion-skyrmion scattering that might be crucial for future applications.